La práctica de las técnicas del mindfulness en episodios de ansiedad y depresión - Miranda Palacios, Vyrghinia Elisa (2022)
Early intervention is important in cases of anxiety and depression since these psychological problems have been increasing in recent years. Before the pandemic, prevalence levels were worrying due to the proportion of people who presented these symptoms, however, since the start of the pandemic, cases of depression have increased by approximately 53.2 million more cases and for anxiety by 76.2 million. (Santomauro, 2021). The approach of psychotherapeutic techniques that demonstrate scientific evidence such as mindfulness are necessary to be able to calm the exponential growth of these cases, therefore, the objective of this study is to identify if the application of Mindfulness techniques reduces the symptoms of anxiety episodes and depression in adolescents, youth and adults. The PRISMA methodology (Page et al., 2021) was used for the recruitment and analysis of the documents found in relation to the proposed objective. According to the analysis of the 10 investigations, significant changes have been evidenced in the results for the reduction of episodes of anxiety and depression in an age range of 12 to 73. Therefore, future programs of intervention in mindfulness for the cases analyzed and verify its effect in the Peruvian context.